2017
DOI: 10.3390/ijms18122568
|View full text |Cite
|
Sign up to set email alerts
|

Volasertib Enhances Sensitivity to TRAIL in Renal Carcinoma Caki Cells through Downregulation of c-FLIP Expression

Abstract: Polo-like kinase 1 (PLK1) plays major roles in cell cycle control and DNA damage response. Therefore, PLK1 has been investigated as a target for cancer therapy. Volasertib is the second-in class dihydropteridinone derivate that is a specific PLK1 inhibitor. In this study, we examined that combining PLK1 inhibitor with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) would have an additive and synergistic effect on induction of apoptosis in cancer cells. We found that volasertib alone and TRAIL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Caspase‐3 and caspase‐9 are important regulatory proteases in the mitochondrial pathway, with caspase‐3 mainly involved in the late stages of apoptosis (Jeon et al, 2017 ; Micucci et al, 2015 ; Wang et al, 2017 ). CytC, located in the outer mitochondrial membrane and mediates cellular mitochondrial apoptosis, plays an important role in mitochondrial energy metabolism by performing electron transfer between respiratory chain complex enzyme III and respiratory chain complex enzyme IV (Liu et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Caspase‐3 and caspase‐9 are important regulatory proteases in the mitochondrial pathway, with caspase‐3 mainly involved in the late stages of apoptosis (Jeon et al, 2017 ; Micucci et al, 2015 ; Wang et al, 2017 ). CytC, located in the outer mitochondrial membrane and mediates cellular mitochondrial apoptosis, plays an important role in mitochondrial energy metabolism by performing electron transfer between respiratory chain complex enzyme III and respiratory chain complex enzyme IV (Liu et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that TRAIL and a DR5 agonist, AD5-10, cleave c-FLIP in H460 cells (24). In human renal carcinoma Caki cells, TRAIL has been reported to downregulate c-FLIP expression and induce apoptosis (25). Mcl-1, an anti-apoptotic Figure 4.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, some of the agents that their combined using with TRAIL has been acceptable outcomes but in limited cell lines have been listed below. kurarinone (Seo et al, ; Zhou, Cao, Wang, & Wu, ), monensin (Yoon et al, ), paxiline (Kang et al, ), diclofenac/hyaluronic acid (Dic/HA) (Fecker et al, ), nickel2+ (Schmidt et al, ), SHetA2 (Lin et al, ), BAY 11–7085 (Shen et al, ), compound c (Jang et al, ), FAK inhibitor PH11 (Dao et al, ), caffeic acid phenethyl ester (CAPE) (Li, Wu, et al, ), fasudil (Wang et al, ), cathepsin S inhibitor ZFL (Seo et al, ), 4‐(4‐Chloro‐2‐methylphenoxy)‐N‐hydroxybutanamide (CMH) (Bijangi‐Vishehsaraei, Huang, Safa, Saadatzadeh, & Murphy, ), actinomycin (Haimerl, Erhardt, Sass, & Tiegs, ), H1 (derivative of tetrandrine) (Lin, Wang, et al, ), genistein (Siegelin, Siegelin, Habel, & Gaiser, ), icaritin (Han, Xu, et al, ), ABT‐737 and VX–680 (Choi et al, ), 6‐shogaol (Han, Woo, et al, ), cathepsin E (Yasukochi, Kawakubo, Nakamura, & Yamamoto, ), ozarelix (Festuccia et al, ), transglutaminase 2 inhibitor (TGM2I) (Li, Xu, Bai, Chen, & Lin, ), amurensin G (Kim, Kim, Lee, et al, ), volasertib (Jeon et al, ), temozolomide (TMZ) (Zhitao, Long, Jia, Yunchao, & Anhua, ), chalcone‐24 (Xu et al, ), gingerol (Lee, Kim, Jung, Lee, & Park, ), triptolide (Chen et al, ), AKT inhibitor API‐1 (Li, Ren, et al, ), smac mimetic compounds (SMC) (Cheung et al, ), dicoumarol (Park, Min, Choi, & Kwon, ), partenolide (Trang et al, ), Pyrrolo‐1, 5‐benzoxazepine (PBOX) (Nathwani et al, ), embelin (Siegelin, Gaiser, & Siegelin, ), myricetin (Siegelin, Gaiser, Habel, & Siegelin, ), quercetin (Jung, Heo, Lee, Kwon, & Kim, ), silibinin (Son et al, ), epigallocatechin gallate (EGCG) (Abou El Naga et al, ), icariside II (Du et al, ), anisomycin (Seo et al, ), dioscin (Kim, Kim, Park, et al, ), celecoxib (Chen et al, ), micro RNA 126 (MiR‐126) (Zhang, Zhou, Zhu, & Yuan, ), gambognic acid (Ye et al, ), survivin inhibitor YM155 (Woo, Min, Seo, &...…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%